Real-World-Evidence of Digital Health Applications (DiGAs) in Rheumatology: Insights from the DiGAReal Registry - Alexander Albrecht; Jule Taubmann; Ioanna Minopoulou; Lukas Hatscher; Stefan Kleinert; Felix Mühlensiepen; Martin Welcker; Jan Leipe; Nils Schulz; Philipp Klemm; Axel Hueber; Georg Schett; et al. (Rheumatology and Therapy)
Abstract Introduction Prescribable digital health applications (DiGAs) present scalable solutions to improve patient self-management in rheumatology, however real-world evidence is scarce. Therefore, we aimed to assess the effectiveness, usage, and usability of DiGAs prescribed by rheumatologists, as well as patient satisfaction. Methods The DiGAReal registry includes adult patients with rheumatic conditions who received a DiGA prescription. Data at baseline (T0) and the 3-month follow-up (T1) were collected through electronic questionnaires. Study outcomes included DiGA-specific outcome assessments as well as generic outcome assessments, including the Patient Global Impression of Change (PGIC), Patient Activation Measure (PAM®), and the German Telehealth Usability and Utility Short Questionnaire (TUUSQ). Changes between T0 and T1 were analyzed using descriptive statistics and paired tests. Results A total of 191 patients were included between June 2022 and April 2023. Of these, 127 completed the 3-month follow-up, and 114 reported using the prescribed DiGA, with 66% reporting weekly use and 15% completing the full DiGA program. The most commonly prescribed DiGAs targeted pain management (53%). Symptom improvement was reported by 51% of patients using a DiGA, with significant reductions in exhaustion levels (p = 0.03). Significant DiGA-specific improvements were observed for DiGAs addressing back pain (p = 0.05) and insomnia (p = 0.006). However, no overall significant changes were detected in patient activation, health literacy, pain, overall health, or disease activity. Back pain and weight management DiGAs were the most effective, frequently used, and best-rated DiGAs, with symptom improvements reported by 50% to 82% of patients. Conclusion The findings suggest that DiGAs can improve symptom management in rheumatic patients, especially for conditions like back pain and weight control. Further real-world evidence is needed and may support value-based digital health efforts and reimbursement frameworks.